Promoting Well-being of Patients with Mental Illness through Positive Psychology and Mindfulness Interventions - Chung Ho JIM; Guang ZENG; Kam Man WONG (康复学报)
Objective:A sense of "Well-being"is important to individuals' health, especially for those with mental and psychosocial challenges. Therefore, occupational therapists who are working in the psychiatric field always use different treatment modalities to promote individuals'well-being. Positive psychology(PP)and mindfulness have become two of those popular treatment modalities in recent years due to a growing amount of empirical evidences on their efficacies in promoting well-being of individuals. Participants'knowledge in PP and mindfulness, their participation in PP and mindfulness activities and the effect of the program on their well-being were explored.Methods:In a 4-month period, 25 patients who were diagnosed with mental and behavioral disorders according to International Classification of Diseases, 10th Revision of World Health Organization were recruited as program participants. PP activities included showing gratitude and appreciation, working on goals, sharing of positive stories and recording positive experiences. Mindfulness activities included mindful breathing, body scan and mindful eating. A"pre-test"vs."post-test'design was employed to investigate participants'knowledge on PP and mindfulness and their participation in these activities using a questionnaire with a 5-point Likert scale. Participants also completed a satisfaction survey to express their viewpoints towards the program.Results:Pre-post comparison showed a significant increase in knowledge of PP(P<0.05)and mindfulness(P<0.01)and participation of mindfulness activities(P<0.01)of participants. Participants with higher education level(>9 years)showed a significant increase in participation of PP activities(P<0.05).Participants also gave positive feedbacks about the program. They had a more positive attitude, more positive emotions, less negative emotions and less stress after the program, which reflected a promotion of well-being.Conclusion:PP and mindfulness program in occupational therapy was feasible and had positive effects on individuals with mental problems. The program will provide experience reference for other occupational therapists or medical staff.